2001
DOI: 10.1002/ajmg.1491
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue facial resemblance in families and syndrome-affected individuals

Abstract: We investigated soft tissue facial resemblance among relatives with or without syndromes and among related and unrelated individuals diagnosed with the same syndrome. Using correlation coefficients, we compared facial landmark (i.e., three-dimensional coordinate) positions and measurements gained by photogrammetry in various combinations of normal and syndrome-affected individuals. There were fewer significant correlations for the three-dimensional coordinates and measurements between the normal parent-normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The presence of a specific facial pattern in patients with a genetic syndrome indicates that there is consistency in the phenotypic expression of the affected genes. 1 Compared to the recognition of familiar faces, the recognition of a disease-specific facial pattern in unrelated individuals is much more difficult, because it requires the skill to extract such a pattern from the facial appearance that is also influenced by family background and environment. Experienced geneticists can do this relatively well, but computers have so far been unable to do this.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a specific facial pattern in patients with a genetic syndrome indicates that there is consistency in the phenotypic expression of the affected genes. 1 Compared to the recognition of familiar faces, the recognition of a disease-specific facial pattern in unrelated individuals is much more difficult, because it requires the skill to extract such a pattern from the facial appearance that is also influenced by family background and environment. Experienced geneticists can do this relatively well, but computers have so far been unable to do this.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that trisomy 21 alters facial morphology sufficiently to obscure family resemblance completely (Opitz & Gilbert‐Barness, ), although previous quantitative attempts to evaluate facial similarity between individuals with DS and their siblings were inconclusive (Shaner, Peterson, Beattie, & Bamforth, ). In samples of unaffected individuals, the resemblance between relatives is easily recognized by most observers, and different studies have shown that facial dimensions of both osseous and soft tissue are heritable (Baydas, Erdem, Yavuz, & Ceylan, ; Sherwood et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that affect facial appearance include inter-and intra-population differences, sex, and age. As a result of these influences, DS individuals tend to resemble each other, but often also resemble their family members (Shaner et al, 2001). …”
Section: Introductionmentioning
confidence: 99%